GE_GERICHTE PM/119/2013 vom 23. April 2013 - GE Cour de justice (2013)
VOIE DE DROIT; RECOURS(CPP); SUSPENSION DE L'EXÉCUTION DE LA PEINE; JUSTE MOTIF; EXPERTISE | CP.92; CPP.182; CPP.393; CPP.385; CPP.439; LaCP.3; LaCP.36; LaCP.41